Agricultural Communicators in Education - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1981)
Editorial back matter for vol.64, no.2, April-June (1981) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education